Identifikasi Bakteri dan Kapang dalam Proses Pembuatan Bioetanol Menggunakan Campuran Feses Sapi Perah dan Tandan Kosong Kelapa Sawit - Riyanto, Kirana Fairuza; Marlina, Eulis Tanti; Harlia, Ellin (Unpad Press, 2024)
Empty palm bunches are plantation waste with a high fibre content that has potential as a bioethanol raw material. The high lignin content in TKKS requires decomposition treatment with the addition of dairy cow faeces which acts as a lignin degrader due to the presence of cellulolytic bacteria. The initial decomposition phase is the phase where microorganisms play a role in degrading cellulose substrates into glucose needed in the bioethanol fermentation process. This study aims to determine the population and characteristics of bacteria and moulds that play a role in the process of making bioethanol using a mixture of dairy cow faeces and EFB macroscopically and microscopically. This study used descriptive analysis with 4 treatments namely P1 (60% Dairy Cow Feces : 40% EFB), P2 (70% Dairy Cow Feces : 30% EFB), P3 (80% Dairy Cow Feces : 20% EFB), and P4 (90% Dairy Cow Feces : 10% EFB) observations on day 1, 7 and 14 of the initial decomposition phase. The results showed that the highest bacterial population was 11,35 CFU/g in the P1 treatment and the highest mould population was 60 CFU/g. in the P4 treatment. The dominant bacteria are rod-shaped, gram-positive bacteria and the genus Bacillus bacteria. The moulds that play a role in the decomposition process of the mixture of TKKS and dairy cow faeces are Aspergillus, Trichoderma, Penicillium, Rhizopus and Mucor.